Behaviour factors and smartphone addiction among youth in selected public universities in Klang Valley - Munusamy, Kalaivani; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2022)
The smartphone has become an indispensable tool for reshaping human existence and life. Smartphones have been created as a valuable variety of functions and greater movability as a result of the development of smartphones, which has increased the high prevalence of smartphone use, specifically youngsters. Smartphone use is a part of digital technologies, like internet, and it has been expected to have a comparable impact, mainly on youth. People are becoming addicted or dependent on smartphones as a result of its appealing and convenient features, as well as their multipurpose function, to the point where a day without smartphone use seems to them to be an incomplete day. However, such social issues seem to elicit less attention from academicians, resulting in poor understanding of the topic. As a result, this research aims to identify behaviour factors on smartphone usage and determine the relationship between behavior factors and smartphone addiction among youths. There were employed survey method in this study. The research was carried out on 400 youths from four public universities in Klang Valley. The finding identified most of the respondents spent more that 12 hours on Internet usage. Based on the result concluded smartphone addiction is correlated with behavior factors namely loneliness, shyness, and stress. Higher assessment on the Internet tie-up on smartphone addiction. To mitigate the negative consequences, it is suggested that government need to give serious attention and must come out with prevention strategies focusing on attitudes that helping youths to set limits for their smartphone accessibility. Apart from that, future studies require different group of respondents and widen range of geographical scope in identifying smartphone users’ behaviors and mental health issues.